RanGTP-Binding Protein NXT1 Facilitates Nuclear Export of Different Classes of RNA In Vitro - Ossareh-Nazari, Batool (American Society for Microbiology, 2000)
To better characterize the mechanisms responsible for RNA export from the nucleus, we developed an in vitro assay based on the use of permeabilized HeLa cells. This new assay supports nuclear export of U1 snRNA, tRNA, and mRNA in an energy- and Xenopus extract-dependent manner. U1 snRNA export requires a 5′ monomethylated cap structure, the nuclear export signal receptor CRM1, and the small GTPase Ran. In contrast, mRNA export does not require the participation of CRM1. We show here that NXT1, an NTF2-related protein that binds directly to RanGTP, strongly stimulates export of U1 snRNA, tRNA, and mRNA. The ability of NXT1 to promote export is dependent on its capacity to bind RanGTP. These results support the emerging view that NXT1 is a general export factor, functioning on both CRM1-dependent and CRM1-independent pathways of RNA export.